2001
DOI: 10.1002/1521-3749(200104)627:4<715::aid-zaac715>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Das unterschiedliche Reaktionsverhalten von basefreiem Tris(trimethylsilyl)methyl-Lithium gegenüber den Trihalogeniden der Erdmetalle und des Eisens

Abstract: Professor Josef Goubeau in memoriamInhaltsu È bersicht. Basefreies Tris(trimethylsilyl)methyl-Lithium, Tsi±Li, reagiert mit den Trihalogeniden der Erdmetalle (MHal 3 mit M = Al, Ga, In und Hal = Cl, Br, I) prima È r unter Bildung der Metallate [Tsi±MHal 3 ]Li. Vor allem mit den schwereren Halogeniden von Ga und In findet aber mit u È berschu È ssigem Tsi±Li zusa È tzlich zur simplen Metathese gleichzeitig auch eine Methylierung statt, die in unterschiedlichem Maûe die Mono-und Dimethylverbindungen Tsi±M(Me)Hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 13 publications
(28 reference statements)
1
47
0
Order By: Relevance
“…All DFT calculations were carried out with the program package ORCA 2.8 28. The calculated structure reproduces well those experimentally determined by XRD analyses12 as well as by single‐crystal X‐ray analyses 13. The derived electron density for the Fe[C(SiMe 3 ) 3 ] 2 , as predicted by theory, is illustrated in Figure 1 (b).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…All DFT calculations were carried out with the program package ORCA 2.8 28. The calculated structure reproduces well those experimentally determined by XRD analyses12 as well as by single‐crystal X‐ray analyses 13. The derived electron density for the Fe[C(SiMe 3 ) 3 ] 2 , as predicted by theory, is illustrated in Figure 1 (b).…”
Section: Resultssupporting
confidence: 77%
“…Thus, as highlighted recently in the literature,11 maximizing the height of the spin‐reversal barrier U by focusing only on maximizing S T , represents a somewhat limiting approach towards future implementation of such molecules in functional devices. Looking at the known SIMM systems containing d‐block metal ions reported in the literature, the two‐coordinate (C–Fe–C) linear molecule Fe[C(SiMe 3 ) 3 ] 2 certainly represents the archetype of the intriguing examples in which it is observed as an unusual metal coordination motif, see Figure 1 (a) 12,13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, B and C). The Co-C and Zn-C interatomic distances of 2.066(2) and 1.995(3) Å, respectively, are similar to the Fe-C separation of 2.0505( 14) Å in Fe(C(SiMe 3 ) 3 ) 2 (12) and the Zn-C separation of 1.982(2) Å in Zn(C(SiMe 3 ) 3 ) 2 (21). In addition, the Co•••O distance of 3.1051(11) Å and the Zn•••O distance of 3.1240(16) Å are substantially longer than the sum of cobalt or zinc and oxygen ionic radii (~2.2 Å), suggesting minimal interactions.…”
Section: Resultsmentioning
confidence: 63%
“…2,5 A two-coordinate iron complex with the bulky tris(trimethylsilyl)methyl ligand, {Fe[C(SiMe 3 ) 3 ] 2 }, was reported by Locke and co-workers. 1 Power et al reported the unexpected stability of another homoleptic two-coordinate complex, {Fe[OC 6 H 3 -2,6-(C 6 H 3 -2,6-i Pr 2 ) 2 ]}. Amazingly, the latter complex was prepared directly from Fe(C 6 H 3 -2,6-(C 6 H 3 -2,6-( i Pr 2 ) 2 ) 2 and O 2 !…”
Section: ■ Introductionmentioning
confidence: 99%